2003
DOI: 10.1556/comec.4.2003.2.9
|View full text |Cite
|
Sign up to set email alerts
|

Application of the intermediate disturbance hypothesis to flooding

Abstract: We examine literature on flooding as a disturbance on both sessile and mobile organisms. The limitations and assumptions of the Intermediate Disturbance Hypothesis (IDH) are identified and examined. We conclude that research on plants supports the IDH. In contrast, mobile invertebrates and vertebrates rarely support the hypothesis. Therefore, we strongly encourage investigators to consider explanations beyond the IDH when explaining community dynamics following floods.Abbreviation: IDH-Intermediate Disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Ephemeral stream is one of the most common natural disturbances, but the effects of the ephemeral stream on plant communities in terms of species diversity and plant species distribution remains poorly studied [10, 11, 14]. In humid and semi-humid regions, it has been reported that stream has degraded soil properties, species diversity and ecosystem stability, which resulted in stunted growth and sometimes mortality of the plants due to erosion and waterlogging [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ephemeral stream is one of the most common natural disturbances, but the effects of the ephemeral stream on plant communities in terms of species diversity and plant species distribution remains poorly studied [10, 11, 14]. In humid and semi-humid regions, it has been reported that stream has degraded soil properties, species diversity and ecosystem stability, which resulted in stunted growth and sometimes mortality of the plants due to erosion and waterlogging [10].…”
Section: Discussionmentioning
confidence: 99%
“…Ephemeral stream is one of the most common natural disturbances, and hence can strongly affect plant species diversity, plant growth characteristics and distribution via two main ways in arid desert regions [913]. The first reason is soil erosion, which indicates that the undeveloped or shallow-rooted plants may be washed away by the ephemeral stream, thereby the community is mainly constructed from developed-rooted plants in washes [10, 14]. The second reason is soil amelioration, which indicates erosion and collision amongst gravel, and hence soil organic matter and mineral nutrients wrapped in stream can be deposited into soils during the process of channel flow events [7, 12].…”
Section: Introductionmentioning
confidence: 99%
“…By Crandall et al (2003) flooding may increase the diversity of mobile vertebrates in affected areas by providing and renewing resources as it increase the variety and abundance of food.…”
Section: Raspravamentioning
confidence: 99%
“…For seabed or benthic communities, as already noted above, the effect of a disturbance varies within a community depending on the characteristics of the disturbance as well as the biological characteristics or traits of the impacted organisms. For example, the more mobile the organism the greater its likelihood of escaping the disturbance altogether, either by being able to burrow below the area impacted by the event (in the case of small organisms) or leave the area altogether (in the case of larger megafaunal organisms) (Crandall et al, 2003). Additionally, small mobile organisms can sometimes burrow upwards when disturbances bury them rather than being smothered (Maurer et al, 1986;Nichols et al, 1978;Tiano et al, 2020).…”
Section: Introductionmentioning
confidence: 99%